Pembelajaran Kooperatif dalam Pendidikan Fisika: Sistematik Literatur Review - Ayu, Hena Dian; Rismawati, Astri Yuni; Kristiyaningsih, Else; Wulandari, Elvina Tri; Wahyuningtyas, Astri; Hudha, Muhammad Nur (Teaching, Learning, and Development, 2023)
Abstract: Learning activities can occur effectively and be fun for students if the teacher can apply a learning model centered on their students. Student interest in learning in class is also influenced by the teacher's ability to manage the class and use appropriate learning models. One strategy for enlivening classroom learning can be done by applying a cooperative learning model. In this research, a literature study was carried out using the Systemic Literature Review (SLR) method from Scopus data sources. A total of 21 articles have been studied with a focus on the effect of applying the cooperative learning model in physics classes on learning outcomes, learning skills, collaboration, communication, concept mastery, process involvement, problem-solving, and training leadership. The study results show that cooperative learning is effectively implemented in physics learning and can improve learning outcomes, study skills, collaboration, communication, mastery of concepts, process involvement, problem-solving, and leadership training. Abstrak: Kegiatan pembelajaran dapat berlangsung secara efektif dan menyenangkan bagi siswa apabila guru dapat menerapkan model pembelajaran yang berpusat kepada peserta didiknya. Ketertarikan peserta didik terhadap pembelajaran di kelas juga dipengaruhi oleh kemampuan guru dalam mengelola kelas dan penggunakan model pembelajaran yang sesuai. Salah satu strategi menghidupkan pembelajaran dikelas dapat dilakukan dengan menerapkan model pembelajaran kooperatif. Pada penelitian ini dilakukan sebuah studi literatur dengan metode Systemic Literature Review (SLR) dari sumber data Scopus. Sebanyak 21 artikel telah dikaji dengan fokus bahasan pada pengaruh penerapan model pembelajaran kooperatif di kelas fisika terhadap hasil belajar, keterampilan belajar, kerjasama, komunikasi, penguasaan konsep, keterlibatan proses, pemecahan masalah, dan melatih kepemimpinan. Hasil kajian menunjukkan bahwa pembelajaran kooperatif efektif diterapkan dalam pembelajaran fisika dan mampu meningkatkan hasil belajar, keterampilan belajar, kerjasama, komunikasi, penguasaan konsep, keterlibatan proses, pemecahan masalah, dan melatih kepemimpinan.